Studies on Germination Behaviour and Longevity of Woodfordia fruiticosa, Kurz Seeds - Bhagat, Surjan; Singh, Virendra; Singh, Ombir (Indian Forester, 1992)
The germination behaviour and longevity of Woodfordia fruiticosa seeds were studied. The results indicated that the germination in sand was significantly better than that of brick powder and soil, respectively and the seeds stored at normal room conditions showed a decline in viability from 96.00% initially to 1.25% in twelve months.